Preparation method of copper-chromium-silicon-titanium alloy and copper-chromium-silicon-titanium alloy wire
Copper-chromium silicon-titanium alloy is prepared by directed solidification continuous casting method, eliminating lateral grain boundaries and forming fibrous crystal structure, solving the problem of insufficient stress relaxation resistance of existing alloys and significantly improving its performance stability.
Patent Information
- Application Number
- CN202411973249.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
In the existing copper-chromium silicon-titanium alloy preparation methods, the stress relaxation resistance is poor, which limits its promotion in connector applications.
The copper-chromium silicon-titanium alloy is prepared by the directional solidification continuous casting method, including smelting, continuous casting, drawing and aging treatment steps. Through this method, the transverse grain boundaries are basically eliminated and the fiber crystal structure is formed, which improves the stress relaxation resistance of the alloy.
By eliminating lateral grain boundaries and forming fibrous crystal structures, the stress relaxation resistance of copper-chromium silicon-titanium alloy is significantly improved, and its performance stability in connector applications is improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nonferrous metal preparation, and in particular to a preparation method of a copper-chromium-silicon-titanium alloy and a copper-chromium-silicon-titanium alloy wire. Background Art
[0002] With the rapid development of electronic communications, transportation, aerospace and other fields, the application demand for copper alloy materials for connectors is increasing, and higher requirements are also placed on their performance. Not only are materials required to have high strength and high conductivity, but they also need to have excellent stress relaxation resistance. Stress relaxation is a special deformation process in which elastic strain is continuously converted into plastic strain under the synergistic effect of thermal activation and stress, and is the main factor leading to unstable contact resistance of connectors.
[0003] Copper-chromium-silicon-titanium alloy has the advantages of high strength and high conductivity, and has broad prospects for application in connectors. However, the copper-chromium-silicon-titanium alloy prepared by conventional melting, extrusion and drawing methods has poor stress relaxation resistance, which greatly limits its promotion and application. Therefore, it is necessary to study and develop a method for preparing copper-chromium-silicon-titanium alloy with high stress relaxation resistance.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method of a copper-chromium-silicon-titanium alloy and a copper-chromium-silicon-titanium alloy wire, so as to improve the stress relaxation resistance of the copper-chromium-silicon-titanium alloy.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a method for preparing a copper-chromium-silicon-titanium alloy, comprising the following steps:
[0008] Smelting, melting raw materials including copper, chromium, silicon and titanium to obtain a melt;
[0009] Continuous casting: forming a copper-chromium-silicon-titanium alloy rod blank by continuous casting in an inert gas atmosphere;
[0010] Drawing, drawing the copper-chromium-silicon-titanium alloy rod blank to form a wire;
[0011] Aging treatment, performing aging treatment on the wire in an inert gas atmosphere and cooling with the furnace to obtain the copper-chromium-silicon-titanium alloy wire, wherein the aging treatment temperature is 400° C. to 500° C. and the time is 1 to 3 hours.
[0012] In an optional embodiment, the raw material includes, by mass fraction, 0.2%-0.5% chromium, 0.02%-0.07% silicon, 0.01%-0.5% titanium, and the remainder copper and unavoidable impurities.
[0013] In an optional embodiment, the raw materials include cathode copper, pure titanium, copper-chromium master alloy and copper-silicon master alloy.
[0014] In an optional embodiment, the chromium content in the copper-chromium master alloy is 10% to 15%;
[0015] And / or, the silicon content in the copper-silicon master alloy is 20% to 40%.
[0016] In an optional embodiment, in the smelting step, the smelting temperature is 1400° C. to 1500° C., and the vacuum degree is 0.001 Pa to 0.1 Pa.
[0017] In an optional embodiment, in the continuous casting step, the continuous casting speed is 1.5 cm / min-5 cm / min.
[0018] In an optional embodiment, in the continuous casting step, the water inlet temperature is 20°C-30°C, and the water flow rate is 0.5LPM-3LPM.
[0019] In an alternative embodiment, the drawing step temperature is 12°C-35°C.
[0020] In a second aspect, the present invention provides a copper-chromium-silicon-titanium alloy wire, which is prepared by the method described in any one of the aforementioned embodiments.
[0021] In an alternative embodiment, the diameter is 3mm-4mm.
[0022] The present invention has the following beneficial effects:
[0023] 1. The present invention substantially eliminates transverse grain boundaries through the method of directional solidification and continuous casting, greatly improving the axial extension and deformation processing capability of the copper-chromium-silicon-titanium alloy, which is beneficial to improving production efficiency and reducing production costs.
[0024] 2. The copper-chromium-silicon-titanium alloy prepared by the present invention has a fibrous crystal structure. Since the impurity content between the fiber grain boundaries is small and the probability of recrystallization nucleation is small, during the aging treatment, the probability of the grain boundary serving as the nucleation core is greatly reduced, thereby increasing the recrystallization temperature of the alloy, which is beneficial to improving the stress relaxation resistance of the copper-chromium-silicon-titanium alloy. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0026] The present invention provides a method for preparing a copper-chromium-silicon-titanium alloy, comprising the following steps:
[0027] Smelting, melting raw materials including copper, chromium, silicon and titanium to obtain a melt;
[0028] Continuous casting: forming a copper-chromium-silicon-titanium alloy rod blank by continuous casting in an inert gas atmosphere;
[0029] Drawing, drawing the copper-chromium-silicon-titanium alloy rod blank to form a wire;
[0030] Aging treatment, performing aging treatment on the wire in an inert gas atmosphere and cooling with the furnace to obtain the copper-chromium-silicon-titanium alloy wire, wherein the aging treatment temperature is 400° C. to 500° C. and the time is 1 to 3 hours.
[0031] The invention substantially eliminates the transverse grain boundary through the method of directional solidification continuous casting, greatly improves the axial extension deformation processing capability of the copper-chromium-silicon-titanium alloy, and is beneficial to improving production efficiency and reducing production cost.
[0032] At the same time, the copper-chromium-silicon-titanium alloy prepared by the present invention has a fibrous crystal structure. Since the impurity content between the fiber grain boundaries is small, it is not conducive to recrystallization nucleation. During the aging treatment process, the probability of the grain boundary serving as the nucleation core is reduced, the recrystallization temperature of the alloy is increased, which is beneficial to improving the stress relaxation resistance of the copper-chromium-silicon-titanium alloy.
[0033] In the present application, the temperature of the aging treatment is 400°C to 500°C, specifically 400°C, 420°C, 440°C, 460°C, 480°C, 500°C or any value between 400°C and 500°C; the time is 1h to 3h, specifically 1h, 2h, 3h or any value between 1h and 3h. If the aging treatment temperature is too high or the time is too long, the precipitate phase will grow and aggregate, which will lead to a decrease in the stress relaxation resistance.
[0034] In an optional embodiment, the raw material includes, by mass fraction, 0.2%-0.5% chromium, 0.02%-0.07% silicon, 0.01%-0.5% titanium, and the remainder copper and unavoidable impurities.
[0035] The dosage of each component has an important influence on the performance of copper-chromium-silicon-titanium alloy. In particular, silicon mainly improves the alloy's resistance to stress relaxation through solid solution strengthening, second phase precipitation and grain boundary purification, while titanium relies more on precipitation strengthening, grain refinement and grain boundary purification to improve the alloy's resistance to stress relaxation.
[0036] In an optional embodiment, the raw materials include cathode copper, pure titanium, copper-chromium master alloy and copper-silicon master alloy.
[0037] In an optional embodiment, the chromium content in the copper-chromium master alloy is 10% to 15%;
[0038] And / or, the silicon content in the copper-silicon master alloy is 20% to 40%.
[0039] Using master alloy as raw material is beneficial to improving the uniformity of the melt, reducing segregation, reducing the introduction of non-metallic inclusions, and is conducive to obtaining better organizational structure and performance consistency.
[0040] In an optional embodiment, in the smelting step, the smelting temperature is 1400° C. to 1500° C., and the vacuum degree is 0.001 Pa to 0.1 Pa.
[0041] Melting under this condition is conducive to ensuring that all components are completely dissolved and fully mixed, and at the same time, some gases and inclusions can be removed, which is crucial to improving the alloy's resistance to stress relaxation.
[0042] In an optional embodiment, in the continuous casting step, the continuous casting speed is 1.5 cm / min-5 cm / min.
[0043] During the continuous casting step, the continuous casting speed will affect the surface quality of the ingot and is within the range of 1.5cm / min-5cm / min. Specifically, it can be 1.5cm / min, 2cm / min, 3cm / min, 4cm / min, 5cm / min or any value between 1.5cm / min-5cm / min. It can take into account both the ingot quality and the production efficiency. If the continuous casting speed is too fast, it will lead to an increase in surface defects of the ingot and reduce the stress relaxation resistance.
[0044] In an optional embodiment, in the continuous casting step, the water inlet temperature is 20°C-30°C, and the water flow rate is 0.5LPM-3LPM.
[0045] The water inlet temperature can be 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, and the water flow rate can be 1LPM, 2LPM, 3LPM, 4LPM, 5LPM; the water inlet temperature and water flow rate will affect the cooling rate, and then affect the grain size and the type, quantity, size and distribution of the precipitated phase. In this application, rapid cooling is conducive to the formation of a fine and uniform grain structure, which can not only improve the hardness of the alloy, but also improve the stress relaxation resistance by reducing grain boundary scattering.
[0046] In an alternative embodiment, the drawing step temperature is 12°C-35°C.
[0047] An embodiment of the present invention further provides a copper-chromium-silicon-titanium alloy wire, which is prepared by the method described in any one of the aforementioned embodiments.
[0048] In an alternative embodiment, the diameter is 3mm-4mm.
[0049] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0050] Example 1
[0051] This embodiment provides a method for preparing a copper-chromium-silicon-titanium alloy wire with a diameter of 3 mm, which specifically includes the following steps:
[0052] Cathode copper, pure titanium, copper-chromium and copper-silicon intermediate alloy are used as raw materials, wherein 0.2% chromium, 0.07% silicon, 0.1% titanium and the remainder of copper and inevitable impurities in the raw materials are melted at a vacuum degree of 0.1 Pa and 1500° C.; copper-chromium-silicon-titanium alloy ingots are directionally solidified and continuously cast in an argon atmosphere, with a continuous casting speed of 1.5 cm / min, a water inlet temperature of 30° C. and a water flow rate of 0.5 LPM; the copper-chromium-silicon-titanium alloy ingots are drawn at room temperature to a diameter of 3 mm; the copper-chromium-silicon-titanium alloy wires drawn at room temperature are subjected to aging treatment in an argon atmosphere, with an aging treatment temperature of 400° C. for 3 hours and a cooling method of furnace cooling.
[0053] Example 2
[0054] This embodiment provides a method for preparing a copper-chromium-silicon-titanium alloy wire with a diameter of 3.6 mm, which specifically includes the following steps:
[0055] Cathode copper, pure titanium, copper-chromium and copper-silicon intermediate alloy are used as raw materials, wherein 0.5% chromium, 0.02% silicon, 0.01% titanium and the remainder of copper and inevitable impurities in the raw materials are melted at a vacuum degree of 0.001Pa and 1400°C; copper-chromium-silicon-titanium alloy ingots are directionally solidified and continuously cast in an argon atmosphere, with a continuous casting speed of 1.5cm / min, a water inlet temperature of 20°C and a water flow rate of 3LPM; the copper-chromium-silicon-titanium alloy ingots are drawn at room temperature to a diameter of 3.6mm; the copper-chromium-silicon-titanium alloy wires drawn at room temperature are subjected to aging treatment in an argon atmosphere, with an aging treatment temperature of 500°C for 1h and a cooling method of furnace cooling.
[0056] Example 3
[0057] This embodiment provides a method for preparing a copper-chromium-silicon-titanium alloy wire with a diameter of 4 mm, which specifically includes the following steps:
[0058] Cathode copper, pure titanium, copper-chromium and copper-silicon intermediate alloy are used as raw materials, wherein 0.3% chromium, 0.03% silicon, 0.5% titanium and the rest copper and inevitable impurities in the raw materials are melted at a vacuum degree of 0.01 Pa and 1450° C.; a copper-chromium-silicon-titanium alloy ingot is directionally solidified and continuously cast in an argon atmosphere, with a continuous casting speed of 2 cm / min, a water inlet temperature of 25° C. and a water flow rate of 1 LPM; the copper-chromium-silicon-titanium alloy ingot is drawn at room temperature to a diameter of 4 mm; the copper-chromium-silicon-titanium alloy wire after room temperature drawing is subjected to aging treatment in an argon atmosphere, with an aging treatment temperature of 450° C. for 2 hours and a cooling method of furnace cooling.
[0059] Comparative Example 1
[0060] The only difference between this comparative example and Example 1 is that non-vacuum melting casting is used to replace the continuous casting step. The specific steps of the process are: first, smelting at 1500°C in an atmospheric environment and then casting into an ingot; then hot forging into a rod at 930°C; then quenching at 950°C and drawing to an outer diameter of 3mm; finally, aging treatment temperature is 400°C, time is 3h, and cooling method is furnace cooling.
[0061] Comparative Example 2
[0062] The only difference between this comparative example and Example 1 is that the aging treatment step is omitted.
[0063] Comparative Example 3
[0064] The only difference between this comparative example and comparative example 1 is that the aging treatment step is omitted.
[0065] Comparative Example 4
[0066] The only difference between this comparative example and Example 1 is that the continuous casting speed is 8 cm / min, the water inlet temperature is 15° C., and the water flow rate is 4 LPM.
[0067] Comparative Example 5
[0068] The only difference between this comparative example and Example 1 is that the continuous casting speed is 0.5 cm / min, the water inlet temperature is 18° C., and the water flow rate is 5 LPM.
[0069] Comparative Example 6
[0070] The only difference between this comparative example and Example 1 is that the aging treatment temperature is 350° C. and the time is 6 h.
[0071] Comparative Example 7
[0072] The only difference between this comparative example and Example 1 is that the aging treatment temperature is 550° C. and the time is 0.5 h.
[0073] The stress relaxation resistance of the copper-chromium-silicon-titanium alloy wires prepared in the above embodiments and comparative examples was tested. The test results are shown in Table 1. The test method refers to the GB / T 10120-2013 standard.
[0074] Table 1 Stress relaxation resistance of copper-chromium-silicon-titanium alloy wire
[0075] Stress relaxation rate at room temperature 100℃ stress relaxation rate 200℃ stress relaxation rate Example 1 6.3 8.7 9.7 Example 2 7.5 9.7 10.8 Example 3 7.1 8.9 9.8 Comparative Example 1 9.5 11.8 14.2 Comparative Example 2 10.2 13.6 15.7 Comparative Example 3 11.3 14.5 16.2 Comparative Example 4 8.3 11.6 14.5 Comparative Example 5 9.1 12.3 14.4 Comparative Example 6 8.5 10.2 12.1 Comparative Example 7 8.8 10.9 12.8
[0076] It can be seen from Table 1 that the copper-chromium-silicon-titanium alloy wire prepared within the parameter range of the method of the present invention has a lower stress relaxation rate at different temperatures than the wire prepared under other parameters, indicating that the copper-chromium-silicon-titanium alloy wire prepared by the method of the present invention has better stress relaxation resistance.
[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a copper-chromium-silicon-titanium alloy, characterized in that: The following steps are involved: Smelting, melting raw materials including copper, chromium, silicon and titanium to obtain a melt; Continuous casting: forming a copper-chromium-silicon-titanium alloy rod blank by continuous casting in an inert gas atmosphere; Drawing, drawing the copper-chromium-silicon-titanium alloy rod blank to form a wire; Aging treatment, aging treatment is performed on the wire in an inert gas atmosphere and furnace cooled to obtain a copper-chromium-silicon-titanium alloy wire, wherein the aging treatment temperature is 400° C. to 500° C. and the time is 1 to 3 hours.
2. The method for preparing the copper-chromium-silicon-titanium alloy according to claim 1, characterized in that: Calculated by mass fraction, the raw material includes 0.2%-0.5% chromium, 0.02%-0.07% silicon, 0.01%-0.5% titanium and the remainder of copper and inevitable impurities.
3. The method for preparing the copper-chromium-silicon-titanium alloy according to claim 1, characterized in that: The raw materials include cathode copper, pure titanium, copper-chromium master alloy and copper-silicon master alloy.
4. The method for preparing the copper-chromium-silicon-titanium alloy according to claim 3, characterized in that: The chromium content in the copper-chromium master alloy is 10% to 15%; And / or, the silicon content in the copper-silicon master alloy is 20% to 40%.
5. The method for preparing the copper-chromium-silicon-titanium alloy according to claim 1, characterized in that: In the smelting step, the smelting temperature is 1400° C. to 1500° C., and the vacuum degree is 0.001 Pa to 0.1 Pa.
6. The method for preparing the copper-chromium-silicon-titanium alloy according to claim 1, characterized in that: In the continuous casting step, the continuous casting speed is 1.5 cm / min-5 cm / min.
7. The method for preparing the copper-chromium-silicon-titanium alloy according to claim 1, characterized in that: During the continuous casting step, the water inlet temperature is 20°C-30°C, and the water flow rate is 0.5LPM-3LPM.
8. The method for preparing the copper-chromium-silicon-titanium alloy according to claim 1, characterized in that: The temperature of the drawing step is 12°C-35°C.
9. A copper-chromium-silicon-titanium alloy wire, characterized in that: Prepared by the method according to any one of claims 1 to 8.
10. The copper-chromium-silicon-titanium alloy wire according to claim 9, characterized in that: The diameter is 3mm-4mm.
Citation Information
Patent Citations
Copper-chromium-titanium alloy contact wire and preparation method thereof
CN103966475A
Stress relaxation resistant high-strength high-elasticity copper alloy and preparation method thereof
CN114457256A
Method of manufacturing ingot for manufacturing ti-containing copper alloy plate or bar of excellent workability
JP2004160543A
Method for manufacturing copper alloy sheet material
JP2015187308A
Cu-ni-si system alloy
US20100000637A1